Murciélagos del Ecuador: un análisis de sus patrones de riqueza, distribución y aspectos de conservación - Burneo, Santiago F.; Tirira, Diego G. (THERYA, 2014)
Introduction: The knowledge of the distribution of bat species in Ecuador has changed significantly in recent years, from new records to taxonomic revisions that have shaped distribution maps to a broader biogeographic understanding. A review of the richness patterns and potential distribution of bats in Ecuador is presented, based on the analysis of records published or stored in scientific collections using Ecological Niche Modeling (ENM) tools. Although maps resulting from ENM are limited both because of the lack of equilibrium and limitations on the representativeness of samples, they constitute a better depiction of distribution than minimal convex polygons or altitudinal ranges. According to the Ecuadorian Red List, 19 species of bats are currently threatened, mainly because of habitat conversion as a consequence of recent colonization, so a better understanding of distribution and spatial richness will result in better proposals for research-priority and conservation-priority areas. Methodology: The analysis was based on 21,455 records, corresponding to 162 species. This information was reviewed and validated using Geographic Information Systems. A maximum entropy algorithm implemented in Maxent was used to evaluate and generate potential distribution models of the species. Those species with insufficient data to generate a model or for which the evaluation was unsatisfactory were eliminated from the analysis. The remaining species models were used to create a composite map representing the richness of bat species for Ecuador, which in turn was used to assess the conservation status of bat diversity in the country. Results: Following review and validation of the data, 10,916 records were used to determine the potential distribution of 81 species of bats, based on ENM. A map of potential bat species richness was obtained for the country with the overlap of the models, representing areas that due to climatic conditions, allow a higher or lower species richness of bats living in sympatry. We determined that the central and north-eastern foothills of the Andes are the most suitable areas enclosing the highest richness of bats in Ecuador. Research-priority and conservation-priority areas were identified. Discussion and conclusions: Information on protected areas of Ecuador was overlaid on top of the potential richness map, showing that only 5.6% of the area with the greatest potential bat richness is protected. Accordingly, we determine the existing information gaps and identify priority areas for research and conservation of bats in Ecuador. Three research-priority areas were defined: (1) the Southeastern tropics, between Pastaza and Morona Santiago provinces; (2) the Northern Andes towards the cordilleraâ€™s western slopes; and (3) areas of the Western dry tropical forests, between the provinces of Guayas and Manabí. Three conservation priority areas were defined:(1) northwest from the province of Pichincha with patches of forest sufficiently large and connected to be protected; (2) most of the Pastaza province, south of the Yasuní National Park; and (3) from the central region of the Morona Santiago province to the northern half of the province of Zamora, towards the Peruvian border to the east. Key words: Amazonia, deforestation, modeling, priority areas, protected areas, scientific collections.